Correlation between Secreted Aspartyl Protease-5 (SAP5) on Increasing Vaginal Acidity in Vulvovaginal Candidiasis - Nur Sophia Matin; Regina Ayu Fristiyanti; Safrina Dewi Ratnaningrum; Nurdiana Nurdiana; Sanarto Santoso; Bambang Rahardjo (Ikatan Dokter Indonesia Wilayah Jawa Timur, 2023)
Introduction: Vulvovaginal candidiasis (VVC) is an infection of the vaginal mucosa that extends to the vulva due to excessive growth of Candida albicans, causing a progressive decrease of Lactobacillus spp., as the main of normal flora. Decrease in the number of Lactobacillus spp. causes a reduction of lactic acid production that it was causing increasing vaginal pH. The increase in pH is due to the progressive growth of C. albicans colonies in the vaginal mucosa. In addition, the mechanism of candidiasis is also influenced by the secretion of virulence factors by C. albicans. Secreted Aspartyl Protease-5 (SAP5) is the dominant virulence factor that plays a role in changing the morphology of yeast cells into hyphae. This study aims to identify the correlation between SAP5 levels and vaginal pH. Material and Methods: This research was conducted in vivo using a sample of Rattus norvegicus with a posttest randomized experimental group design approach. This study has two groups, i.e., Negative Control (NC) and Positive Control group (PC). SAP5 and pH samples were taken from vaginal fluids and then measured using ELISA and a digital pH meter. The statistical analysis used was Pearson Correlation to analyze the correlation between SAP5 and pH levels. Results: There was a strong correlation (R=0.846) that means the increase of SAP5 is related to the increase of vaginal acidity in the PC group. Conclusion: The increase in SAP5 levels is directly followed by an increase in the pH value of vaginal fluids,